The predictive value of serum SCUBE1, CLEC-2 and UCP2 in acute ischemic stroke after intravenous thrombolysis: Serum SCUBE1, CLEC-2 and UCP2 in acute ischemic stroke - Sun, Chunying; Liu, Zongmei; Qin, Hongling; Li, Fangcun; Liang, Ni; Gao, Chao; Chen, Wei; Hu, Yueqiang; Zhang, Ding (Journal of Medical Biochemistry, 2025)
Objective: To analyze the predictive value of serum signal peptide-CUB-epidermal growth factor domain-containing protein 1 (SCUBE1), C-type lectin-like receptor-2 (CLEC-2), and uncoupling protein 2 (UCP2) for poor outcome following intravenous thrombolysis (IVT) in patients who have experienced an acute ischemic stroke (AIS). Methods: A total of 116 AIS patients who received IVT treatment in this hospital from June 2023 to October 2024 were selected as the observation group, and the control group consisted of an additional 116 healthy people who were examined physically in this institution over the same time period. The patients were divided into good prognosis and poor prognosis groups according to the modified Rankin scale (mRS) score. After IVT, the factors predicting poor outcome in AIS patients were examined using multivariate logistic regression. The prognostic significance of serum SCUBE1, CLEC-2, and UCP2 for poor prognosis in AIS patients following IVT was examined using a receiver operating characteristic (ROC) curve. Results: While the observation group’s serum UCP2 level was lower than the control group’s, the observation group’s levels of SCUBE1 and CLEC-2 were higher. P<0.05 indicated that the differences were statistically significant. There were 75 patients in the good prognosis group and 41 patients in the poor prognosis group. While serum UCP2 levels were lower than those in the good prognosis group (P<0.05), the percentage of patients with infarction regions >4 cm³ and the levels of serum SCUBE1 and CLEC-2 were higher in the bad prognosis group than in the good prognosis group. According to multivariate logistic regression analysis, increased blood levels of SCUBE1 and CLEC-2 were associated with a poor prognosis for AIS patients following IVT (P<0.05), and higher blood UCP2 levels were protective factors against a poor outcome in AIS patients following IVT (P<0.05). The areas under the curve (AUCs) of serum SCUBE1, CLEC-2, and UCP2 alone for predicting a poor prognosis were found by the ROC curve analysis after IVT in AIS patients were 0.752, 0.694, and 0.776. SCUBE1, CLEC-2, and UCP2 had lower AUCs than the three indicators together, which had an AUC of 0.861. The AUC predicted separately (Z(3-item combination -SCUBE1)=2.358, Z(3-item combination -CLEC-2) =2.714, z 3-item combination -UCP2=2.591, P=0.018, 0.007, 0.010). Conclusion: The levels of serum SCUBE1 and CLEC-2 in AIS patients with poor prognosis after IVT increase, whereas the level of UCP2 decreases. The combined detection of these three indicators has high predictive value for the poor prognosis of AIS patients after IVT.